Prevalence of Hypertension (HTN) and Cardiovascular Risk Factors in a Hospitalized Pediatric Hemophilia Population. Issue 3 (April 2018) - Alperstein, Warren; Corrales-Medina, Fernando F.; Tamariz, Leonardo; Palacio, Ana M.; Davis, Joanna A.
Abstract : Improved life expectancy in hemophilia has led to a greater interest in age-related disorders. Hypertension (HTN) as well as cardiovascular disease have been increasingly reported in hemophilic adults but there is currently very limited data in the pediatric population. We conducted a cross-sectional study using data from the 2012 National Health Cost and Utilization Project database to determine the prevalence of HTN and associated cardiovascular risk factors in a hospitalized pediatric hemophilia population, between the ages of 0 to 21 years, in comparison with the general pediatric population. The prevalence of HTN was significantly higher in children with hemophilia (CWH) in comparison with the general pediatric population (1.71% vs. 1.02%, P -value=0.005). When adjusting the analysis for sex, the prevalence of HTN in the hemophilia cohort remained higher, although not statistically significant (1.52% vs. 1.22%, P -value=0.2568). When examining the concomitant presence of ≥1 cardiovascular risk factors in the hypertensive subgroups, CWH had a higher prevalence of obesity (2.64% vs. 1.32%, P -value <0.0001). Interestingly, diabetes mellitus was more prevalent in nonhemophilic children (1.47% vs. 0.56%, P -value=0.0015). These data suggest that cardiovascular risk factors need to be closely monitored in CWH, and a better preventive strategy is likely needed to identify those hemophilic patients at higher risk of developing cardiovascular disease in adulthood.